Accreditation in a Sub Saharan Medical School: a case study at Makerere University - Galukande, Moses; Opio, Kenneth; Nakasujja, Noeline; Buwembo, William; Kijjambu, Stephen C.; Dharamsi, Shafik; Luboga, Sam; Sewankambo, Nelson K.; Woollard, Robert (BMC medical education, 2013)
Of more than the 2,323 recognized and operating medical schools in 177 countries (world wide) not all are subjected to external evaluation and accreditation procedures. Quality Assurance in medical education is part of a medical school’s ethical responsibility and social accountability. Pushing this agenda in the midst of resource limitation, numerous competing interests and an already overwhelmed workforce were some of the challenges faced but it is a critical element of our medical profession’s social contract. This analysis paper highlights the process of standard defining for Medical Education in a typically low resourced sub Saharan medial school environment. Methods: The World Federation for Medical Education template was used as an operating point to define standards. A wide range of stakeholders participated and meaningfully contributed in several consensus meetings. Effective participatory techniques were used for the information gathering process and analysis. Results: Standards with a clear intent to enhance education were set through consensus. A cyclic process of continually measuring, judging and improving all standards was agreed and defined. Examples of the domains tackled are stated. Conclusion: Our efforts are good for our patients, our communities and for the future of health care in Uganda and the East African region.
Keywords: Accreditation; Standards; Medical education